Analysis of prayer jurisprudence at the ocean based on the Book of Is'af Ahl al-'Asr bi Ahkam al-Bahr - Agadirun, Nur Diyanah; Abdul Mutalib, Najihah; Embong, Abdul Hanis; Ismail, Ismar Liza Mahani; Ab Halim, Adlina; Hasbullah, Mohd Masyaal (Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao, 2024)
Purpose: This paper aims to analyze the jurisprudence of prayer in the ocean based on the book Is'af Ahl Al-'Asr Bi Ahkam Al-Bahr and identify the problems that often occur when performing prayer. Theoretical framework: This book was chosen because it touches on and discusses the laws of maritime jurisprudence related to prayer. In this book, there are seven main chapters, namely water, purification, prayer, funeral, fasting, zakat and Hajj. Design/methodology/approach: this study does not discuss all chapters in this book but analyzes selected topics according to the problems of prayer that often occur while at sea. This study uses a qualitative method with a library research design, while data collection is done through the study of documents obtained through books, articles and journals related to the research topic. This study also used the method of interviewing respondents involved in research in the ocean to obtain data. Next, the data obtained is analysed using content analysis to obtain accurate research findings. Findings: The study found that the implementation of prayer in the ocean has a method and guide in the Sharia based on the book Is'af Ahl Al-'Asr Bi Ahkam Al-Bahr. Discussion: The responsibility as a Muslim in prayer in the ocean field can be carried out perfectly with the existence of accurate guidance according to Islamic teachings. © 2024 ANPAD - Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao. All rights reserved.